PENGARUH KUALITAS, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN - Aniek Widiarti; Estu Niana Syamiya; Udoh Supriatin (JURNAL LENTERA BISNIS, 2024)
The aim of this research is to determine the influence of quality, price and promotion on consumer purchasing decisions at Mustika Collection Toko Pasar Kemis, especially Nibras Clothing. The method used in this research is a quantitative method. The population of this research was 100 consumers and the research technique used simple random sampling of 80 consumers. The method used in this research uses calculations, multiple regression, descriptive statistics and hypothesis testing. The results of research on the influence of quality, price and promotion on purchasing decisions show quite good results. The results of the regression analysis of quality, price and promotion have a positive influence on purchasing decisions. The hypothesis shows that quality has a positive influence on purchasing decisions, while price and promotion have a negative influence on purchasing decisions. Keywords: Quality; Price; Promotion; Buying decision.